Ways to form professional training of future teachers- psychologists - Nagymzhanova K.M. Нагымжанова К.М.; Nasibek D.D. Насибек Д.Д. (Рroblems of engineering and professional education, 2022)
The article considers the problems of training educational psychologists with professional and personal competencies that contribute to their acquisition of professionally important knowledge. The classification of the concept of professional qualification is given. The theoretical, practical and psychological blocks of training future teachers-psychologists for self-development of professional competencies are highlighted and outlined in detail. Professional education determines the role of pedagogical experience in the formation of professional competencies of teachers-psychologists.